Stratégies pour un vol virtuel : exemple de paysages brésiliens - Alfredo Pereira de Queiroz Filho (Confins)
This paper approaches the two main problems of the virtual flight, spatial orientation and cognitive overload, and proposes strategies to assist in its navigation. To illustrate the research, examples are used to dealing landscapes of the Brazilian territory, as Foz do Iguaçu - PR, Rio de Janeiro - RJ, Pantanal - MS, Salvador - BA, Belém - PA, Manaus - AM and São Paulo - SP